Investigation of Radioactivity Levels and Evaluation of Radiation Hazards in Soil Samples Collected from the Area Extended from Agdabya to Qaminis, Libya. - Elorfi , Saeid Y.; Ali , Waneesah A.; Nagem , Sameh A. (Libyan Journal of Science &Technology, 2025)
In order to initiate a radiological assessment program and to establish a baseline map of radioactivity background levels in the area extended from Agdabya to Qaminis in Libya environment, this study has been adopted to identify the radionuclide contents in the soil of this area. Thirty soil samples were collected at a depth of 5 cm in the area extended from Agdabya to Qaminis, measurement of radioactivity and (pH). Measurement of the radioactivity of the Uranium , Thorium , potassium and Cesium were done at the Atomic Energy Center of Tagora in Libya using Hyper Pure Germanium detector. The average radioactivity concentration for , , were 81.32 Bq/Kg, 32.71Bq/Kg, 184.46Bq/Kg and 2.03Bq/Kg. The variations of the assessed radiological hazard parameters indices , , , , and were found to be as follows: 94.89-258.37, 0.26-0.698, 0.37-1.197, 0.33-0.898, 0.175-0.92 and 42.96-120.03, respectively. The pH values ranged from 7.70 to 9.45, with an average of 8.44.